Adoptive parentage, legal means for surrogacy: Regarding the Judgement of the Suprem Court of 31st March 2022 - Castellanos Ruiz, Mª José (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The judgement of the Suprem Court of 31st March 2022, following the same line of interpretation of its Judgment of of 6th february 2014, has rejected, on appeal, the recognition of natural filiation in favor of a Spanish woman in relation to a child born through a surrogacy contract entered into in Mexico.The Chamber, however, establishes the adoptive affiliation of said minor born in Mexico to a woman,to whom male and female germ cells from anonymous donors were implanted, so that the childlacked a biological link with the plaintiff, a Spanish woman, single.This sentence is especially relevant because, although the recognition of natural filiation is rejected,adoptive filiati n is being allowed, as it is one of the modalities contemplated in our legal system, as theSupreme Court (TS) revealed in its previous sentence; but in addition, the guidelines that the EuropeanCourt of Human Rights (ECHR) has been entrusting in relation to surrogacy contracts through its jurisprudence are being respected. When the most appropriate thing would have been that, if the conditionsfor the formalization of the adoption were not met, the Supreme Court had granted the request made bythe plaintiffs, as the French judge finally did in the Mennesson case, and proceeded to recognize naturalfiliation in favor of the intending mothe .In any case, the reality is that, either through natural affiliation or through adoptive affiliation, theaffiliation of minors born abroad as a result of surrogacy contracts is being recognized. Therefore, a modification of the regulations on the matter would be appropriate, so that, in a systematic way, the existingregulations do not have to be applied by analogy or that they are not complying with the laws on adoption
Keywords: surrogacy; surrogate mothers; surrogate motherhood; conflict-of-laws; recognition and enforcement of foreign decisions; foreign birth certificates; lex fori; parentage; Private international law; Forum Shopping; evasion of the law; international public policy; european public policy; interests of the child